The best American short stories, 2025 : selected from U.S. and Canadian magazines - Acampora, Lauren; Anderson, Sarah; Binder, Emma; Braunstein, Sarah, 1976-; Dess, Sophie Madeline; Di Iorio, Lyn; Fang, Isabelle; Johnston, Bret Anthony, 1971-; Kingsley-Ma, Hannah; Lohier, William; Majeed, Yasmin Adele; McCracken, Elizabeth; et al. (Best American series., 2025)
"A collection of the year's best American short stories, selected by celebrated bestselling author Celeste Ng, author of Everything I Never Told You and Little Fires Everywhere, and series editor Nicole A. Lamy. 'Short stories can act like little tuning forks, helping us to clarify our own values,' writes guest editor Celeste Ng. 'In a time when our values are being tested daily, it's hard to think of anything more important.' The twenty pieces in The Best American Short Stories 2025 upend expectations and test the foundation of our beliefs. From a bereaved medical actress obsessed with a student in her rotation to a mysterious sickness that ignites a lethal running mania in its victims, and from the grounds of a wild animal estate to a celebrity look-alike mother for hire, these stories transport readers to the impossible edges of our world and vivify characters who reflect the spectrum of human experience. The pieces in this collection helped series editor Nicole A. Lamy 'make more sense of the world than real life was able to provide.' Within the wild and varied universes that grow from the constraints of the story form, ordinary life seems beguiled and enchanted spaces hold unshakable truths. Bold, urgent, and ultimately hopeful, The Best American Short Stories 2025, through reflections and refractions, offers readers new ways of seeing the world."--